2016
DOI: 10.5312/wjo.v7.i9.570
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of isolated hand injuries in the United Arab Emirates

Abstract: AIMTo provide suggestions for hand injury prevention by study the demography and risk factors of casualties suffering from isolated hand injuries.METHODSAll trauma patients with isolated hand injuries who were admitted to Al Ain Hospital for more than 24 h during a period of 3 years were studied. Patient demographics, location, mechanism/time of injury, and length of hospital stay were all analyzed.RESULTSTwo hundred and ten patients were studied. Their mean age was 29.7 years. Males constituted 92%. Sixty-fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 28 publications
2
16
3
1
Order By: Relevance
“…Fall of heavy objects and machine injury were leading causes for hand injury in our study which is same as reported by other authors [2,4,6] . Major risk factors for occupational hand injuries were malfunctioning equipment, working overtime, distraction, rush to finish job, lack of protective measures, inexperience, inattention and unfamiliarity with the job allotted [7,8] .…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Fall of heavy objects and machine injury were leading causes for hand injury in our study which is same as reported by other authors [2,4,6] . Major risk factors for occupational hand injuries were malfunctioning equipment, working overtime, distraction, rush to finish job, lack of protective measures, inexperience, inattention and unfamiliarity with the job allotted [7,8] .…”
Section: Discussionsupporting
confidence: 91%
“…In all expatriate male patients injuries occurred at place of work in contrast to Omani nationals where injuries predominantly were due to other causes not related to work place. The percentage of hand injuries and number of males in our study was lower as compared to other studies [1,4,5] . Work place related injuries among young males (21-40 years) accounted for majority of injuries followed by injuries sustained at home by women and children.…”
Section: Discussioncontrasting
confidence: 89%
See 3 more Smart Citations